2005
DOI: 10.1002/ijc.21553
|View full text |Cite
|
Sign up to set email alerts
|

Impact of race and baseline PSA on longitudinal PSA

Abstract: There is an increasing debate regarding the frequency of prostatespecific antigen (PSA) testing and the current primary screening modality used to detect prostate cancer. The purpose of this study is to determine whether PSA screening intervals should be based on initial PSA. Our study explores longitudinal changes of PSA levels in black and white males separately. Study participants were 768 white and 450 black males attending an annual prostate cancer screening. We fit a longitudinal repeated measures model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
(40 reference statements)
1
16
2
Order By: Relevance
“…The present study suggests that the appropriate cut-off point for tPSA of Iranian men is 7.85 ng/ml, slightly different from those in other countries (9,10). In USA and Europe, men with a tPSA of <2.5 ng/ml have a low probability of having clinically detected prostate cancer (11,12).…”
Section: Discussioncontrasting
confidence: 78%
“…The present study suggests that the appropriate cut-off point for tPSA of Iranian men is 7.85 ng/ml, slightly different from those in other countries (9,10). In USA and Europe, men with a tPSA of <2.5 ng/ml have a low probability of having clinically detected prostate cancer (11,12).…”
Section: Discussioncontrasting
confidence: 78%
“…16,17 Some studies have suggested that men with an initial PSA level ,1 ng ml 21 have a 99% probability of PSA levels remaining normal (,4 ng ml 21 ) for the next 4 or 5 years. 15 In our study, men with an initial PSA level ,1 ng ml 21 had only a 1.88% chance of having PSA levels .4 ng ml 21 and a 2.89% chance of having PSA levels .3 ng ml 21 in the next 4 years. A previous study performed a population-based screening of Japanese men to determine the optimal screening interval for men with PSA levels ,2.0 ng ml 21 .…”
Section: Discussionmentioning
confidence: 45%
“…Similar results were observed in a previous study that evaluated the influence of baseline PSA on longitudinal PSA in black and white patients. 15 In that study, black and white men with a PSA between 3.0 and 3.9 ng ml 21 had a 44.7% and 51.6% chance, respectively, of converting to PSA .4.0 ng ml 21 in the following 4 years. The percentage in our study was even higher.…”
Section: Discussionmentioning
confidence: 86%
“…Prostate cancer is the most common cancer in American men [1][2][3][4][5][6][7][8][9][10][11][12]. The ever-expanding, seemingly conflicting literature on prostate cancer makes counseling patients with prostate cancer a difficult but often necessary part of clinical practice.…”
Section: Opinionmentioning
confidence: 99%
“…As a pathological entity, prostate cancer occurs in almost all men as same report the risk of long term urinary incontinence is 14.4% for the radical surgery group and 4.9% for the radiotherapy group. Patients choosing radiotherapy should understand that the risk of uncomfortable bowel urgency and painful hemorrhoids are more prevalent with radiation than surgery [2]. The authors reminded us that in patients who choose radiation over surgery, performing radical prostatectomy after failure of radiotherapy is difficult and associated with more complications.…”
Section: Opinionmentioning
confidence: 99%